A Prospective, Multicenter, NCI EDRN Study of [-2]proPSA: Improving Prostate Cancer Detection and Correlating with Cancer Aggressiveness - Sokoll, Lori J. (2010)
BACKGROUND: The free PSA isoform, [-2]proPSA, has been shown to be associated with prostate cancer. The study objective was to characterize the clinical utility of serum [-2]proPSA for prostate cancer detection and assess its association with aggressive disease. METHODS: From among 669 subjects in a prospective prostate cancer detection study at four NCI Early Detection Research Network clinical validation centers, 566 were eligible. Serum PSA, free PSA, and [-2]proPSA were measured (Beckman Coulter Access 2 Analyzer). RESULTS: 245 (43%) of the 566 participants had prostate cancer on biopsy. At 70% specificity, sensitivity of %[-2]proPSA ([-2]proPSA/fPSA) was 54% (95% CI:48%–61%, null hypothesis 40%). Including %[-2]proPSA in a multivariate prediction model incorporating PSA and %fPSA improved the performance (p<0.01). In the 2–4 ng/mL PSA range, %[-2]proPSA outperformed %fPSA (ROC AUC= 0.73 vs. 0.61, p=0.01). At 80% sensitivity, %[-2]proPSA had significantly higher specificity (51.6%, 95% CI:41.2%–61.8%) than PSA (29.9%, 95% CI:21.0%–40.0%) and %fPSA (28.9%, 95% CI:20.1%–39.0%). In the 2–10 ng/mL PSA range, a multivariate model had significant improvement (AUC=0.76) over individual PSA forms (p<0.01-<0.0001). At 80% sensitivity, specificity of %[-2]proPSA (44.9%, 95% CI:38.4%–51.5%) was significantly higher than PSA (30.8%, 95% CI:24.9%–37.1%) and relatively higher than %fPSA (34.6%, 95% CI:28.5%–41.4%). %[-2]proPSA increased with increasing Gleason score (p<0.001) and was higher in aggressive cancers (p=0.03). CONCLUSIONS: In this prospective study, %[-2]proPSA demonstrated potential clinical utility for improving prostate cancer detection and was related to the risk of aggressive disease. IMPACT: The addition of %[-2]proPSA could impact the early detection of prostate cancer.